نظام الادارة الالكترونية ودورها في تحقيق الكفاءة الادارية في الهيئة العامة للمعلومات - البيباص د.عبد الرؤوف على; المنتصر د. هلال هدية; القمبري محمد سالم (Aljameai)
Abstract: The electronic management system and its role in achieving administrative efficiency in the Public Information Authority Study Identify the role of electronic management in achieving administrative efficiency. Study its application in the Public Information Authority. This researcher used the descriptive and analytical approach and the study population was chosen from the Public Authority for Information employees who occupy administrative positions, who number (205), and due to the lack of this number due to the circumstances occurring, Stephen Thompson’s law was used to determine the size of the study sample, and the questionnaire was used as a main tool for data collection And information, where (54) questionnaires were distributed to the study members (the study sample), and (54) questionnaires were retrieved, i.e. 100%. The study found a set of results, the most important of which are: The results showed that there is agreement to a large degree of study members on the reality of applying the electronic management system in the Public Authority for Information, as the relative weight reached (69.44), and the presence of approval from the study members on the existence of a large degree in achieving administrative efficiency in the Public Authority for Information, where the relative weight reached (78.00%). The study reached a set of recommendations, the most important of which are: Increasing interest in providing clear and comprehensive scientific policies to keep pace with contemporary technological changes, working on electronic connectivity between the headquarters of the Authority and the sectoral information centers. Key words: electronic management, administrative efficiency